UNDERSTANDING FEMINISM BY READING LITTLE WOMEN - Alice Juana Anggara (Universitas 17 Agustus 1945 Semarang, 2021)
Feminist movement has widely been mistaken as a male-hating campaign. Louisa May Alcott was taking part in this movement by her literary works and the most famous work was Little Women (1868). The analysis of this book expanded the comprehension of the matter of feminism, coping with the misunderstanding about feminism among readers. The researcher took a close look into Little Women qualitatively, by focusing on one of the main protagonists, who is also a feminist, namely Josephine March, and the alteration of her character during her lifetime.Keywords: feminism, womanhood, gender inequality, literature, equalize opportunity.